Risk-return preferences, gender inequalities and the moderating role of a counselling intervention on choice of major : evidence from a field and survey experiment - Fervers, Lukas [Verfasser]; Jacob, Marita [Verfasser]; Beckmann, Janina [Verfasser]; Piepenburg, Joachim G. [Verfasser] (My University, 2024)
„In this study, we examine gender inequalities in educational decision-making. Specifically, we consider high school students selecting a higher education study programme and examine gender-specific risk and return preferences regarding monetary returns and the risk of failure in the programme. Moreover, we assess whether a counselling intervention can mitigate these gender inequalities. We employ a research design that combines a factorial survey and a field experiment to test our hypotheses. Consistent with our theoretical expectations, the results of the factorial survey confirm that girls are disproportionally deterred by the higher failure rates of possible study programmes, whereas boys are attracted more strongly by higher expected returns after graduation. Overall, the counselling intervention reduces the dissuasive effect of higher failure rates. Contrary to our expectations, the moderating effect is not stronger for girls but (if at all) is stronger for boys.“ (authors‘ abstract; BIBB-Doku)
Keywords: P 2.1 Schulabgänger; S 1.4 Hochschulbildung; G 2.4.5 Gender Mainstreaming; 370; 300; Gymnasiast; Schulabgänger; Studienfachwahl; Entscheidungsfindung; Geschlechtsspezifische Faktoren; Bildungsberatung; Studienberatung; Einflussfaktor